Chromosome 4q25 variants and recurrence after second-generation cryoballoon ablation in patients with paroxysmal atrial fibrillation. (1st October 2017) - Miyazaki, Shinsuke; Ebana, Yusuke; Liu, Lian; Nakamura, Hiroaki; Hachiya, Hitoshi; Taniguchi, Hiroshi; Takagi, Takamitsu; Kajiyama, Takatsugu; Watanabe, Tomonori; Igarashi, Miyako; Kusa, Shigeki; Niida, Takashi; et al.
Abstract: Background: Chromosome 4q25 single-nucleotide polymorphisms (SNPs) are associated with atrial fibrillation (AF) recurrence after radiofrequency catheter ablation, however the underlying mechanism is unknown. Pulmonary vein (PV) reconnections are common post-radiofrequency ablation. We explored the pre-procedural parameters, including AF susceptibility SNPs, predicting the response to PV isolation (PVI) using second-generation cryoballoons. Methods: One hundred fifty-seven paroxysmal AF patients undergoing PVI using second-generation cryoballoons and genetic testing were enrolled. The top 6 AF-associated Japanese ancestry SNPs were evaluated. Fourteen-day consecutive monitoring was performed to detect AF recurrences. Results: Early recurrence of AF (ERAF) was detected in 74(47.1%) patients, and the AF-free survival at 12-months after single procedures was 72.1%. Cox's proportional models determined that higher pro-BNP values (hazard ratio [HR] = 1.001; 95% confidence interval [CI] = 1.000–1.001; p = 0.003) and the rs1906617 risk allele (HR = 2.440; 95% CI = 1.062–5.605; p = 0.035) were independently associated with ERAFs, and the rs1906617 risk allele (HR = 4.339; 95% CI = 1.044–18.028; p = 0.043) was the sole factor significantly associated with AF recurrence. Second procedures were performed in 41 patients a median of 6.0[5.0–9.5] months later, and 42/162(25.9%) PVs were reconnected. Reconnections were similarly observed in rs1906617 risk allele carriers and wild-type patients. Risk allele carriers at rs1906617 were more likely to have non-PV foci, but did not reach statistical significance (10/35 vs. 0/6, p = 0.132). Conclusions: AF risk alleles on chromosome 4q25 modulated the risk of AF recurrence after PVI using second-generation cryoballoons in patients with paroxysmal AF. Our study results suggested that non-PV foci might be the more likely mechanism of a high AF recurrence in chromosome 4q25 variant carriers.